Analysis of Re-purchase Intention by Hybrid Rice Seed Farmers - Hadimartono, Soesilo; Sumarwan, Ujang; Sanim, Bunasor (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2017)
Rice demand will continue to increase along with the project rate of population increase. The use of quality seed was the thing to get attention. Therefore, it is necessary to analyze the factors that affect the interest in the purchase of hybrid rice seeds by farmers. The analysis showed that the factors affecting the purchase of hybrid rice seed is the attitude, subjective norm and perceived behavior control. Perceived behavioral control or perceived behavior control according to respondents, it is a factor that determines the first to affect the level of the purchase of hybrid rice seeds. A further factor affecting is subjective norm then the last one is the attitude. Purchase behavior of hybrid rice by farmers in the marketing area Region I Sukamandi PT Sang Hyang Seri is influenced by the contact farmer who can be contacted, the suggestion of extension local hybrid rice, and the influence of most small marketing is done by PT Sang Hyang Seri itself. Variables influence the perception of control behavior which is in contrary to existing theories. The analysis showed a negative influence, that is, it is possible for farmers who are in the hybrid rice production center. In addition, the general marketing of rice farmers in the region Region I Sukamandi PT Sang Hyang Seri using rice seeds last in 2014, in which time was the existence of government subsidies that encourage farmers to use hybrid seeds in order to increase national rice production.